Chapter 5 Visible, valued and included Prioritising youth participation in policy-making for the Irish LGBTI+ National Youth Strategy - Ceatha, Nerilee (Taylor & Francis, 2021)
This co-created chapter explores the involvement of the authors in the development of the Irish LGBTI+ National Youth Strategy 2018-2020: LGBTI+ young people: visible, valued and included. More specifically, it provides rich insights of two youth co-authors' experience of participating on the Youth Advisory Group for the Strategy. Their reflective commentary draws on previously undocumented learning and provides examples of the innovative initiatives which sought to ensure LGBTI+ youth were also visible, valued and included in the policy-making process. By placing LGBTI+ young people front and centre, the potential for holistic and lived experience to inform strategic planning was enhanced, reflecting the breadth and diversity of this experience. The development of the Strategy showcases the potential of creative policy-making processes underpinned by child-centred, rights-based approaches. While collaboration in policy-making with young people is essential, the complexities and challenges of participation highlight the need for consideration of the practicalities of implementing meaningful participatory processes. The importance of interpersonal and institutional allyship are discussed throughout the chapter, with the youth co-authors providing real-world examples. The chapter concludes with an appeal to strengthen dialogue and feedback, enhancing the influence of seldom-heard youth on policy-making. In this way, participation ensures policy-making speaks directly to young people's interests and concerns.